A policymaking perspective on international business and the natural environment - Gölgeci, Ismail; De Marchi, Valentina; Kolk, Ans; Kunisch, Sven; Demirbag, Mehmet (Springer, 2026)
Multinational enterprises are central to today’s economy, simultaneously driving environmental pressures and holding capabilities to mitigate them. What matters for policymaking is how cross-border firms that orchestrate global value chains shape environmental outcomes that spill over borders, and how policy mixes can steer behaviors. We advance a policymaking perspective, framework, and research agenda on the international business–natural environment nexus. They direct scholars to specify geo-physical, geo-economic, and geo-political linkages; trace how policy instruments shape firm responses, how these scale into system trajectories, and how feedback/feedforward loops alter policy and strategy over time and across places; and unravel emerging tensions.
Keywords: Multinational corporations (MNCs) and enterprises (MNEs); Environmental issues; Regulation; Global value chains; Sustainability; Governance; fi=InnoLab|en=InnoLab|; fi=Kansainvälinen liiketoiminta|en=International Business|